Gender Equality in the Digital Age: Exploring Women's Empowerment, Digital Entrepreneurship, and Financial Inclusion in Emerging Markets - Dey, Amrita (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
This study examines the intersection of gender equality, digital entrepreneurship, and financial inclusion in emerging markets. Through mixed-methods analysis of data from Asian, African, and Latin American economies (2011-2025), we establish that gender-responsive digital financial inclusion (GDFI) significantly enhances women's economic empowerment and household welfare. Our constructed GDFI Index reveals that every 10% improvement correlates with a 2.1% increase in female entrepreneurship and a 1.8% reduction in household poverty. Barriers include persistent digital access gaps (54% lower internet usage among South Asian women), limited venture capital (2% for women-led startups), and entrenched sociocultural norms. This study proposes an integrated framework that combines digital public infrastructure development, gender-lens investing, and policy reforms to accelerate progress toward SDGs 5 and 8. The findings underscore the US$1.7 trillion opportunity to bridge the women's MSME financing gap, while highlighting the critical role of women-centric digital ecosystems.